Application of new plasma coatings for restoration of the surface of material - Shаrovka, V.; Шаровка, В. (Харківський національний автомобільно-дорожній універститет, 2024)
The study analyzed powder materials to obtain wear-resistant coatings. Field tests for wear resistance were conducted using the method of friction between two surfaces. The tests were carried out on the universal test bench SMC-2 at a rotation speed of 200 rpm. A pressure of 100 kgf was applied to the test sample. The wear resistance test cycle comprised 200,000 revolutions, with lubrication provided through the drop method. Special powders were used in the experiment, including PG-SR3, PN55T45, and PR-Ni70Cr17S4R4 + 20% PT-Al5N with a PT-Al5N underlayer. The selection of wear-resistant coatings was based on the analysis of the following properties: adhesion strength of the coating to the base material, wear resistance of the coatings, hardness, and porosity. Metallographic analysis of the structure of plasma coatings obtained from powders PGSR3, PN55T45, and PR-Ni70Cr17S4R4 + 20% PT-All5N with three different plasma heater power levels (10 kW, 15 kW, and 20 kW) indicated that the densest and most reliable coating among those studied is the coating made from PR-Ni70Cr17S4R4 + 20% PT-Al5N powder. Therefore, there is no need to increase the heater power beyond 15 kW when spraying this type of powder. The research concluded that when obtaining wear-resistant coatings, the optimal choice is PR-Ni70Cr17S4R4 + 20% PT-All5N powder with a PT-Al5N underlayer.
Застосування нових плазмових покриттів для відновлення поверхні матеріалів.
Keywords: plasma coating; wear resistance; properties; structural composition; phase composition.; плазмове покриття; зносостійкість; властивості; структурний склад; фазовий склад.; 620.175.2:669.15